Stent Placement for Acute Superior Mesenteric Artery Occlusion Associated with Type B Aortic Dissection - Kazushi Suzuki; Masashi Shimohira; Takuya Hashizume; Yuta Shibamoto (Case Reports in Vascular Medicine)
A 50-year-old man had a mesenteric ischemia related to superior mesenteric artery (SMA) occlusion associated with a type B aortic dissection. We decided to perform stent placement for the SMA and could avoid mesenteric ischemia. We think the stent placement in the SMA might be an option for the treatment of mesenteric ischemia caused by aortic dissection.